2018
DOI: 10.3389/fimmu.2018.00771
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cells and Their Extracellular Vesicles Enhance the Anti-Inflammatory Phenotype of Regulatory Macrophages by Downregulating the Production of Interleukin (IL)-23 and IL-22

Abstract: Resolution-phase macrophage population orchestrates active dampening of the inflammation by secreting anti-inflammatory and proresolving products including interleukin (IL)-10 and lipid mediators (LMs). We investigated the effects of both human bone marrow-derived mesenchymal stromal cells (MSCs) and MSC-derived extracellular vesicles (MSC-EVs) on mature human regulatory macrophages (Mregs). The cytokines and LMs were determined from cell culture media of Mregs cultivated with MSCs and MSC-EVs. In addition, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 58 publications
3
76
1
Order By: Relevance
“…(47) or prevent the migration of pro-inflammatory M1 macrophages through interaction with chemokine ligands expressed on other tissues and cells (28,41,42,47) (Table 1). In addition, as reported by a study, SC-EVs downregulate the production of IL-23 and IL-22 and upregulate anti-inflammatory prostaglandin E2 (PGE2) by indirectly repressing the function of T helper type 17 (Th17) cell or by inducing conversion of Th17 cells into regulatory T cells (Tregs) (102). As a result, SC-EVs induced conversion of activated regulatory macrophages (Mregs) from a proinflammatory phenotype to an alternative anti-inflammatory phenotype and eventually promoted the reduction of severe inflammation (102).…”
Section: Scs Stem Cells; Evs Extracellular Vesicles; Sc-evs Stem Cmentioning
confidence: 81%
“…(47) or prevent the migration of pro-inflammatory M1 macrophages through interaction with chemokine ligands expressed on other tissues and cells (28,41,42,47) (Table 1). In addition, as reported by a study, SC-EVs downregulate the production of IL-23 and IL-22 and upregulate anti-inflammatory prostaglandin E2 (PGE2) by indirectly repressing the function of T helper type 17 (Th17) cell or by inducing conversion of Th17 cells into regulatory T cells (Tregs) (102). As a result, SC-EVs induced conversion of activated regulatory macrophages (Mregs) from a proinflammatory phenotype to an alternative anti-inflammatory phenotype and eventually promoted the reduction of severe inflammation (102).…”
Section: Scs Stem Cells; Evs Extracellular Vesicles; Sc-evs Stem Cmentioning
confidence: 81%
“…This phenotype change was accompanied with a functional shift in DC cytokine production profile from inflammatory to immunoregulatory. MSC-EVs have been reported to induce regulatory macrophage phenotype change and skew their cytokine production toward a regulatory profile with increased production of anti-inflammatory cytokines and downregulation of inflammatory cytokine production ( 11 , 33 , 38 ). A recent study by Tung et al ( 39 ) also demonstrated that regulatory T cell-derived EVs (Treg-EVs) induced anti-inflammatory cytokine secretion by DCs, with an increased IL-10 and decreased IL-6 production following LPS stimulation ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis revealed that miR-223-3p targets the CD83 gene, while miR-142-3p has been experimentally observed as an inhibitor of IL-6 expression ( 54 ). Recent evidence also showed that Treg-EV enclosed miR-142-3p can be acquired by DCs resulting in the induction of a tolerogenic phenotype in DC ( 38 ). Moreover, miR-126-3p targets genes upstream TLR signaling, such as Tsc1 , a negative regulator of the mTOR kinase ( 55 ) and miR-29b targets Bcl-2 gene, which is involved in the maintenance of DC longevity in vivo ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, using in vitro cell models and an in vivo model of cardiotoxin induced-skeletal muscle injury, Lo Sicco and colleagues demonstrated that adipose tissue derived-MSCs release EVs endowed with potent anti-inflammatory capacities to balance macrophage polarization toward an “M2-like” profile [ 112 ]. More recently, Hyvärinen and coworkers demonstrated that MEx enhance the anti-inflammatory phenotype of regulatory (‘M2-like’) macrophages by downregulating the production of interleukin (IL)-23 and IL-22 [ 113 ]. Of interest, other studies have found that exosomes isolated from MSCs preconditioned by lipopolysaccharide (LPS) may have superior ‘regulatory’ abilities for macrophage polarization and resolution of chronic inflammation by shuttling microRNA let-7b [ 114 ].…”
Section: Modulation Of Macrophage Function: the Gatekeeper Of Exosmentioning
confidence: 99%